Improved social functioning and role functioning in rheumatic patients using a non-verbal communication tool: Results from a randomized, double-blind, controlled pilot-study - Karnik, Julia; Riedl, David; Schirmer, Michael (Frontiers in Medicine, 2023)
Introduction Pain is a leading symptom in patients with rheumatic diseases, limiting not only physical functioning but also social well-being. This study studied the practicability of colored wristbands as non-verbal communication tools and the effects of these tools on social and role functioning in rheumatic patients. Methods This prospective, double-blind, randomized controlled pilot study recruited 110 patients. Practicability of colored silicon wristbands as non-verbal communication tools was assessed by questionnaires. The control group received written information on the rheumatic diseases and their management in general. Social functioning and role functioning were assessed using two subscales from the EORTC QLQ-C30. Results A significant overall improvement of social functioning (p = 0.005) and role functioning (p = 0.001) with medium to large effect size were reported by patients both in the intervention and the control group. Post hoc analyses revealed a significant change in the mean social functioning (p = 0.007) and role functioning scores with medium effect size, while no such effect was found in the control group for neither variable (p = 0.006 and p = 0.06–0.21, respectively). 42.9% of the patients will continue to use a non-verbal communication tool in the future. Practicability of the wristbands was limited by small size of the wristbands in 17.6% and uncomfortable wearing of the wristbands and skin irritation each in 4.4% of the patients. Discussion This study shows first promising results for the use of a non-verbal communication tool in about 50.0% of the patients with rheumatic diseases, to improve their social functioning and role functioning.